Internal Control Systems and Financial Performance. A Case Study of Kabale Municipal Council, Kabale District - Bernard Kabweine, Mwesigwa (Kabale University, 2022)
A Dissertation Submitted in Partial Fulfilment of the Requirements for the Award of a Master’s Degree in Business Administration of Kabale University